Multiplicity of (mini-)jets at small x - Ewerz, Carlo; Webber, Bryan R. (Journal of high energy physics, 1999)
We derive closed expressions for the mean and variance of the (mini-)jet multiplicity distribution in hard scattering processes at low x . Here (mini-)jets are defined as those due to initial-state radiation of gluons with transverse momenta greater than some resolution scale μ R , where Λ 2 << μ R 2 << Q 2 , Λ being the intrinsic QCD scale and Q the momentum transfer scale of the hard scattering. Our results are valid to leading order in log (1/ x ) but include all sub-leading logarithms of Q 2 /μ R 2 . As an illustration, we predict the mini-jet multiplicity in Higgs boson production at the Large Hadron Collider.